2023
DOI: 10.1002/jpen.2498
|View full text |Cite
|
Sign up to set email alerts
|

Home enteral nutrition: A descriptive study

Abstract: Background: With data demonstrating benefit, the prevalence of home enteral nutrition (HEN) has increased significantly over the last few decades. Despite this increase, there remains a paucity of data regarding real-world use of HEN including clinical outcomes and complications.Methods: Descriptive analysis of prospectively maintained database of our specialized HEN program was undertaken. Patients who received care in our program with HEN initiation date between January 1, 2018, and December 31, 2020, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The high prevalence of EFI has always been a concern and is frequently raised in various clinical reviews. A recently presented retrospective analysis of prospectively maintained large HEN cohort noted that one in five patients receiving HEN (20.5%) developed at least one symptom of EFI symptoms interrupting their EN 31 . Gungabissoon et al reported that around one in three patients who were critically ill who received EN developed EFI in a median of 3 days in a retrospective multicenter study evaluating EN‐tolerance profile in >150 ICUs 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of EFI has always been a concern and is frequently raised in various clinical reviews. A recently presented retrospective analysis of prospectively maintained large HEN cohort noted that one in five patients receiving HEN (20.5%) developed at least one symptom of EFI symptoms interrupting their EN 31 . Gungabissoon et al reported that around one in three patients who were critically ill who received EN developed EFI in a median of 3 days in a retrospective multicenter study evaluating EN‐tolerance profile in >150 ICUs 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the effectiveness of HEN in promoting the recovery of gastrointestinal function and enhancing the immune system, practical challenges persist. Variability in self-management skills among patients and caregivers, coupled with the lack of a comprehensive community healthcare service system, often leads to a range of complications in patients receiving HEN, such as diarrhea, gastroesophageal reflux, aspiration, tube occlusion, rupture, displacement, and nutritional intolerance (5)(6)(7). To address these issues, the academic community has conducted numerous studies related to HEN in recent years.…”
Section: Introductionmentioning
confidence: 99%